Rethinking the “Pre” in Pre-Therapy Counseling: No Benefit of Additional Visits Prior to Therapy on Adherence or Viremia in Ugandans Initiating ARVs - Siedner, Mark J.; Lankowski, Alexander; Haberer, Jessica E.; Kembabazi, Annet; Emenyonu, Nneka; Tsai, Alexander C.; Muzoora, Conrad; Geng, Elvin; Martin, Jeffrey N.; Bangsberg, David R. (PLOS ONE, 2012)
Background Many guidelines recommend adherence counseling prior to initiating antiretrovirals (ARVs), however the additional benefit of pre-therapy counseling visits on early adherence is not known. We sought to assess for a benefit of adherence counseling visits prior to ARV initiation versus adherence counseling during the early treatment period. Methods We performed a secondary analysis of data from a prospective cohort of HIV-infected patients in Mbarara, Uganda. Adults were enrolled upon initiation of ARVs. Our primary exposure of interest was ARV adherence counseling prior to initiating therapy (versus concurrent with initiation of therapy). Our outcomes of interest were: 1) average adherence >90% in first three months; 2) absence of treatment interruptions >72 hours in first three months; and 3) Viral load >400 copies/ml at the three month visit. We fit univariable and multivariable regression models, adjusted for predictors of ARV adherence, to estimate the association between additional pre-therapy counseling visits and our outcomes. Results 300 participants had records of counseling, of whom 231 (77%) completed visits prior to initiation of ARVs and 69 (23%) on or shortly after initiation. Median age was 33, 71% were female, and median CD4 was 133 cell/ml. Median 90-day adherence was 95%. Participants who completed pre-therapy counseling visits had longer delays from ARV eligibility to initiation (median 49 vs 14 days, p<0.01). In multivariable analyses, completing adherence counseling prior to ARV initiation was not associated with average adherence >90% (AOR 0.8, 95%CI 0.4–1.5), absence of treatment gaps (AOR 0.7, 95%CI 0.2–1.9), or HIV viremia (AOR 1.1, 95%CI 0.4–3.1). Conclusions Completion of adherence counseling visits prior to ARV therapy was not associated with higher adherence in this cohort of HIV-infected patients in Uganda. Because mortality and loss-to-follow-up remain high in the pre-ARV period, policy makers should reconsider whether counseling can be delivered with ARV initiation, especially in patients with advanced disease.